DEVELOPMENT OF ISLAMIC EDUCATION IN PHILOSOPHY OF EXISTENTIALISM PERSPECTIVE - Jam'ah abidin (AL-FIKRA, 2013)
Theories of human resource development in the context of existentialism really uphold the fundamental principles inherent in every individual. That's, in the development of human resources through the efforts of Islamic Education must provide guarantees of freedom (hurriyyah/liberalism) to all students subject to be imaginative and creative according to their talents and their irâdah (will). For this flow, just the way a subject so students can develop their potential, so they were able to become a man of independent, creative, innovative and dynamic. This guarantees certainly described in the overall of educational system, both in the context of the curriculum, the learning process and the learning environment.